2012
DOI: 10.1007/s10340-012-0420-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and bioactivities of three Chrysanthemum essential oils against Tribolium confusum (du Val) (Coleoptera: Tenebrionidae)

Abstract: Essential oils from three species of Chrysanthemum growing in Tunisia (C. coronarium, C. fuscatum, and C. grandiflorum) were first analyzed by gas chromatography (GC) and GC/mass spectrometry (MS) and then evaluated for toxicity and antifeeding action against Tribolium confusum. The essential oils obtained from leaves and flowers shared a similar qualitative composition, but the relative proportions of the constituents were quite different. The essential oil of C. grandiflorum was rich in sesquiterpenoids, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Essential oils are blends of volatile secondary metabolites from plants; these oils feature a broad-spectrum activity because of the presence of several chemicals [5]. Currently, the main extraction methods for volatile oil from C. morifolium are steam distillation extraction (SDE) [4,5,7], ultrasonic extraction [8], and supercritical carbon dioxide extraction [3]. Different from the above-mentioned extraction methods, headspace solid-phase microextraction (HS-SPME) is simple and reproducible, does not involve solvent use, and includes a short extraction time [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential oils are blends of volatile secondary metabolites from plants; these oils feature a broad-spectrum activity because of the presence of several chemicals [5]. Currently, the main extraction methods for volatile oil from C. morifolium are steam distillation extraction (SDE) [4,5,7], ultrasonic extraction [8], and supercritical carbon dioxide extraction [3]. Different from the above-mentioned extraction methods, headspace solid-phase microextraction (HS-SPME) is simple and reproducible, does not involve solvent use, and includes a short extraction time [9].…”
Section: Introductionmentioning
confidence: 99%
“…The plant's dried flowers contain alkanes, flavonoids, terpenoids, unsaturated fatty acids, polysaccharides, and essential oils [1][2][3][4][5][6][7]. Essential oils are blends of volatile secondary metabolites from plants; these oils feature a broad-spectrum activity because of the presence of several chemicals [5]. Currently, the main extraction methods for volatile oil from C. morifolium are steam distillation extraction (SDE) [4,5,7], ultrasonic extraction [8], and supercritical carbon dioxide extraction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Literature records showed that fumigant efficacy of a number of aromatic and medicinal plant essential oils have been investigated in the laboratories against stored product insect pests including T. castaneum 19,20 . However, reports on the insecticidal activity of T. nubigenum essential oil against stored product pests are meager.…”
Section: Discussionmentioning
confidence: 99%
“…The ionization of the sample components was performed in EI mode of 70 eV. The constituents of oil were identified by calculation of their retention indices under temperature programmed condition for n-alkanes C 8 -C 20 . Identification of individual components was assigned by retention time comparison with authentic components and oil of known composition and by mass spectra with those obtained from Wiley/NIST/ Pfleger Mass Spectral library Version 2.0 f as well as with literature data 11 .…”
Section: Gc and Gc-ms Analysismentioning
confidence: 99%
“…The confused flour beetle, Tribolium confusum Jaquelin du Val (Coleoptera: Tenebrionidae), is a small insect (adults measure 3-6 mm) that commonly infests flour and grain (Haouas et al 2012). Adults of T. confusum used in the experiments were obtained from a population cultured at Auburn University for more than 10 years.…”
Section: Biological Materialsmentioning
confidence: 99%